2021
DOI: 10.15420/ecr.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019: Psychological Stress and Cardiovascular Diseases

Abstract: Minimising deaths due to coronavirus disease 2019 (COVID-19) is a global priority. However, the harmful effects are not limited to those directly related to the infection. The COVID-19 pandemic has also had a serious impact on the mental health of the general population. An increasing number of people are exhibiting signs of depression and an increase in suicides has also been noted around the world. Mental health issues may be linked to starting or increasing the use of addictive substances, such as tobacco, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Several physiological changes, associated with psychological distress during the pandemic, can predispose patients to or worsen cardiovascular disease including increased oxidative stress, catecholamine, cortisol levels, aggregation of platelet, inflammatory cells, endothelial dysfunction, and stimulation of the sympathetic nervous system [ 47 , 48 ]. Anxiety and fear are psychological disorders that can coexist with heart failure and other cardiovascular diseases, and are even considered major risk factors for cardiovascular disease such as coronary artery disease, stress-cardiomyopathy, arrhythmias, stress-cardiomyopathy, myocarditis, cardiogenic shock, and cardiac arrest [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several physiological changes, associated with psychological distress during the pandemic, can predispose patients to or worsen cardiovascular disease including increased oxidative stress, catecholamine, cortisol levels, aggregation of platelet, inflammatory cells, endothelial dysfunction, and stimulation of the sympathetic nervous system [ 47 , 48 ]. Anxiety and fear are psychological disorders that can coexist with heart failure and other cardiovascular diseases, and are even considered major risk factors for cardiovascular disease such as coronary artery disease, stress-cardiomyopathy, arrhythmias, stress-cardiomyopathy, myocarditis, cardiogenic shock, and cardiac arrest [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the serious impact of the pandemic on patients living with COPD or any other pre-existing chronic conditions can rationalize their fear and anxiety. Regular assessment of the patients’ psychological status related to COVID-19, and careful management of pre-existing chronic diseases should be considered as a main component of heart failure management [ 47 ] to assist with the stratification of risks for severe illness [ 59 ]. Thus, frontline health care providers should use reliable media such as governmental television channels and COVID-19 emergency hotlines and valid screening tools to assess the effect of COVID-19 on psychological status such as the anxiety scale [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that COVID-19 can lead to overwhelming stress, addiction to tobacco, alcohol, or increased obesity. "COVID-19 related depression" reflects the condition (58). Pressure from the coronavirus can lead to stress cardiomyopathy or an increased risk of heart failure (59).…”
Section: Analysis Of Reference Co-citationmentioning
confidence: 99%
“…It should be mentioned that the current coronavirus disease 2019 (COVID-19) pandemic has been associated with an increasing burden of CVD risk factors in the population. This may result in future substantial increases in the incidence of CVD ( 11 ). Moreover, it is extremely important to control risk factors for CVD and to manage CVD effectively during the pandemic to improve the prognosis of COVID-19 patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%